2016
DOI: 10.1002/eji.201646596
|View full text |Cite
|
Sign up to set email alerts
|

B‐cell‐intrinsic function of TAPP adaptors in controlling germinal center responses and autoantibody production in mice

Abstract: Control of B-cell signal transduction is critical to prevent production of pathological autoantibodies. Tandem PH domain containing proteins (TAPPs) specifically bind PI(3,4)P2, a phosphoinositide product generated by PI 3-kinases and the phosphatase SHIP. TAPP KI mice bearing PH domain-inactivating mutations in both TAPP1 and TAPP2 genes, Our findings demonstrate a B cell-intrinsic role of TAPP-PI(3,4)P2 interaction in regulating GC responses and autoantibody production and suggest that uncontrolled Akt activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…Because c-myc and PI3K signaling are both essential for GC responses and have been associated with GC B cell selection in the light zone (39,40), it is tempting to speculate that PI3K-and c-myc-dependent activation of glycolysis may help provide a selective growth advantage to high-affinity B cells receiving BCR and T FH cell signals. It is possible that deregulation of glucose transport in TAPP KI mice may allow survival and differentiation of GC B cells that would normally be uncompetitive, accounting for previously observed increases in GC size, polyclonal IgG production and autoantibody production (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because c-myc and PI3K signaling are both essential for GC responses and have been associated with GC B cell selection in the light zone (39,40), it is tempting to speculate that PI3K-and c-myc-dependent activation of glycolysis may help provide a selective growth advantage to high-affinity B cells receiving BCR and T FH cell signals. It is possible that deregulation of glucose transport in TAPP KI mice may allow survival and differentiation of GC B cells that would normally be uncompetitive, accounting for previously observed increases in GC size, polyclonal IgG production and autoantibody production (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that TAPP KI mice develop lupus-like autoimmunity associated with dysregulated GCs (20). Because GC B cells in TAPP KI mice express higher levels of GLUT1 and show elevated glucose uptake, we assessed whether inhibition of glycolysis has any effect on the chronic GCs in middle-aged TAPP KI mice.…”
Section: Impact Of 2-dg Treatment On B Cell Proliferation Chronic Gcmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletion of SHIP in BCR‐transgenic B cells specific for Ars or HEL antigens was found to reverse their anergic phenotype in two models of self‐tolerance . We found that B cells bearing mutations uncoupling the TAPP adaptors from PI(3,4)P 2 were hyper‐active and drive an SLE‐like phenotype , suggesting that proteins binding this SHIP enzymatic product may contribute important regulatory functions. The function of SHIP in maintaining B‐cell tolerance and preventing autoimmunity may be related to its interaction with FcγRIIB, as FcγRIIB deletion in some mouse strains can also cause lupus‐like autoimmunity, but interestingly not the C57BL/6 background used for the above B cell‐specific SHIP deletion studies .…”
Section: Introductionmentioning
confidence: 86%